Copaxone in therapy of remittent disseminated sclerosis patients - O. A. Kitcherova; L. I. Reikhert; S. M. Bychenko; A. A. Sokolova (Бюллетень сибирской медицины)
Twenty three remittent disseminated sclerosis patients have been observed for two years to study the influence of copaxone on clinical manifestations and course of their disease in relation to the state of membrane- destabilizing processes in erythrocytes.